Flexible Solution Approach for Multistage Transmission Network Expansion Planning with Multiple Generation Scenarios - Freitas, Patricia F. S. [UNESP]; Macedo, Leonardo H. [UNESP]; Romero, Ruben [UNESP] (Springer, 2020)
One of the approaches to represent competitive market rules, uncertainties in the generation, and different seasonal climatic conditions in the multistage transmission network expansion planning problem is through scenario-based modeling, by considering several generation scenarios. However, the investment costs of the solutions obtained by this type of approach are much higher when compared to the costs of the expansion plans provided by a single-scenario formulation. To overcome this issue, this work presents a flexible solution approach based on a mixed-integer linear programming formulation, which generates a pool of high-quality solutions with reasonable investment costs and small operating infeasibilities for the problem. The proposed method is evaluated using the IEEE 24-bus system and the southern Brazilian 46-bus system. The results indicate that the proposed approach can provide solutions with acceptable investment costs and small infeasibilities in the operation of the system, which can be easily corrected in the short- and medium-term expansion planning.
Keywords: Mixed-integer linear programming; Multiple generation scenarios; Multistage planning; Optimization; Transmission network expansion planning